2016
DOI: 10.1016/j.avb.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Aggression replacement training (ART) for reducing antisocial behavior in adolescents and adults: A systematic review

Abstract: Objective: Aggression Replacement Training (ART) is a multimodal program aiming at replacing antisocial behaviors by actively teaching desirable behaviors. The program is frequently used and has been provided within a wide variety of settings, but its effectiveness in its own right has not been addressed in previous reviews. This systematic review examines the effect of ART on antisocial behavior in young people and adults. Methods: Published and unpublished literature was searched to identify randomized and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 27 publications
3
44
0
3
Order By: Relevance
“…Apart from the previous, preliminary Swedish SPPS report, the remaining three studies in theBrännström et al (2016) review altogether included 244 "treated" offenders. Apart from the previous, preliminary Swedish SPPS report, the remaining three studies in theBrännström et al (2016) review altogether included 244 "treated" offenders.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the previous, preliminary Swedish SPPS report, the remaining three studies in theBrännström et al (2016) review altogether included 244 "treated" offenders. Apart from the previous, preliminary Swedish SPPS report, the remaining three studies in theBrännström et al (2016) review altogether included 244 "treated" offenders.…”
mentioning
confidence: 99%
“…Although initial evaluation suggested encouraging results for ART (Goldstein & Glick, 1987), later reports indicated mixed effectiveness in reducing recidivism, self-control, social skills, or moral development for children and adolescents (Brännström et al, 2016;Hornsveld, Kraaimaat, Muris, Zwets, & Kanters, 2014). To our knowledge, there are very few informative outcome evaluations of ART for adult offenders.…”
mentioning
confidence: 99%
“…Therefore, Goldstein et al's analyses and subsequent conclusions may not be representative of ART effectiveness in real-world settings. In a meta-analysis of all ART programs reported in the literature between 1987 and 2014, Brannstrom et al (2016) could only find 16 studies of ART as a stand-alone program and the methodological quality was limited. Half of these studies were reported by researchers with vested interest in the outcomes.…”
Section: Limitations In Existent Researchmentioning
confidence: 99%
“…Further, as there were no consistencies in evaluation measures used (recidivism was primary outcome measure and change in any of the three domains-anger control, social skill and moral reasoning-were secondary outcomes) or timing of assessments, a statistical meta-analysis was not possible. Brannstrom et al (2016) concluded that ART only seems successful in that it is wide-spread and frequently used for offender populations and recommended that more reliable and valid research methodology be used to explore the specific components of ART with clearly defined target groups and well established protocols.…”
Section: Art Effectiveness Researchmentioning
confidence: 99%
See 1 more Smart Citation